Research on the City Network of Guangdong, Hongkong and Macao from the Perspective of Information Flow: Analysis based on Baidu Index - Qixuan Wang; Min Zhao (Journal of Regional and City Planning, 2018)
In the context of the rapid development of informatization and globalization, the theoretical methods of urban scholars have shifted from a 'space of places' appraoch, which looks at geographical areas, to a 'space of flows' approach, which is based on flows of people, goods, capital, and information between cities. The rapid development of the Internet makes the connections between cities more dynamic than ever before. The subject of this study are cities in three provincial administrative units in Southern China: Guangdong, Hong Kong and Macao. The development of the Internet provides an opportunity to analyse the relationships between the cities in this region from the viewpoint of information flow. Using the area distribution model in Baidu Index (a website of the Baidu company), this study recorded the web search volume, simulated the information flows, and analysed the network correlation degrees between the cities in Guangdong, Hong Kong and Macau. The conclusions are: (1) from the perspective of information flow, the city network in Guangdong, Hong Kong and Macao has a clear 'core-periphery' structure, which amplifies the difference in urban hierarchy between big and small cities; (2) the cities in the traditional Pearl River Delta core region have a stronger ability to aggregate information flows and geographical proximity reflects information flow; (3) information flows between the cities in Guangdong and Hong Kong and Macao are not smooth, and thus needs to be improved.Keywords. City network; area of Guangdong-Hongkong-Macau; information flow; Baidu Index.Abstrak. Dalam konteks perkembangan informatisasi dan globalisasi yang pesat, metode teoritis para peneliti perkotaan telah bergeser dari pendekatan 'ruang tempat' yang melihat wilayah geografis, ke pendekatan 'ruang arus' yang didasarkan pada arus manusia, barang, kapital, dan informasi antar kota. Pesatnya perkembangan internet membuat hubungan antar kota lebih dinamis dari sebelumnya. Subyek penelitian ini adalah kota-kota di tiga unit administrasi provinsi di Cina Selatan: Guangdong, Hong Kong, dan Macao. Perkembangan Internet memberi kesempatan untuk menganalisis hubungan antara kota-kota di wilayah ini dari sudut pandang arus informasi. Dengan menggunakan model distribusi area pada indeks Baidu (sebuah situs perusahaan Baidu), makalah ini mencatat jumlah pencarian web, mensimulasikan arus informasi, dan menganalisis tingkat korelasi jaringan di antara kota-kota di Guangdong, Hong Kong dan Macau. Kesimpulannya adalah: (1) Dari perspektif arus informasi, jaringan kota di Guangdong, Hong Kong dan Macao memiliki struktur 'inti-pinggiran' yang jelas, yang memperkuat perbedaan dalam struktur hirarki perkotaan antara kota-kota besar dan kecil; (2) Kota-kota di wilayah inti Pearl River Delta tradisional memiliki kemampuan yang lebih kuat untuk mengumpulkan arus informasi dan kedekatan geografis juga mencerminkan arus informasi; (3) Arus informasi antara kota-kota Guangdong dan Hong Kong dan Macao tidak lancar, sehingga perlu ditingkatkan.Kata Kunci. Jaringan kota; wilayah Guangdong-Hongkong-Macau; arus informasi; Indeks Baidu.